Optical component with surface protective film, optical laminate, and method for manufacturing an optical device

JP2026169232APending Publication Date: 2026-10-16NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2026173509
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0012】 本発明の実施形態による表面保護フィルム付き光学部材は、薄型化が求められる光学デバイスの製造過程に好適に使用でき、該表面保護フィルム付き光学部材を用いてレーザ加工を行うと、該レーザ加工後に該表面保護フィルムを再剥離して露出した光学部材の加工端部における隆起が抑制され、品質不良品の発生を低減できる。また、そのような表面保護フィルム付き光学部材を備えた光学積層体を提供することができる。さらに、そのような表面保護フィルム付き光学部材を用いた、光学デバイスの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169232000001_ABST
    Figure 2026169232000001_ABST
Patent Text Reader

Abstract

This invention provides an optical component with a surface protective film that can suppress the protrusion of the processed edges of a thin optical component when laser processing the optical component. It also provides an optical laminate equipped with such an optical component with a surface protective film. Furthermore, it provides a method for manufacturing an optical device using such an optical component with a surface protective film. [Solution] An optical member with a surface protective film according to an embodiment of the present invention is an optical member with a surface protective film comprising a surface protective film (I) and an optical member, wherein the surface protective film (I) comprises a substrate (Ia) and an adhesive layer (Ib), the adhesive layer (Ib) and the optical member are directly laminated, the thickness of the optical member is 400 μm or less, and the thickness of the substrate (Ia) is less than 60 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical member with a surface protective film, an optical laminate, and a method for manufacturing an optical device.

Background Art

[0002] In order to impart rigidity and impact resistance to an optical member included in an optical device, a reinforcing film (a reinforcing base material provided with an adhesive layer) may be bonded in advance to the surface (typically, the exposed surface) of the optical member for reinforcement (Patent Documents 1 to 3).

[0003] Reinforcing films are usually intended for permanent adhesion, and are different from surface protective films generally used as process materials, that is, films that are temporarily and tentatively attached during situations such as assembly, processing, and transportation of devices and the like, and are re-peeled before the use of the devices and the like. For this reason, the adhesive constituting the adhesive layer of the reinforcing film is usually designed to realize permanent adhesion.

[0004] In recent years, thinning of optical devices represented by organic EL panels, LCD panels, touch panels and the like has been required. On the other hand, the reinforcing film for optical members finally remains in the optical device. Therefore, the reinforcing film for an optical member included in an optical device that is required to be thinned is not limited to merely being able to exhibit a reinforcing effect, and is also required to be thin.

[0005] In the manufacturing process of an optical device, a step of laser processing the optical member to which the above-described reinforcing film is bonded may be included. In this laser processing, laser is usually irradiated from the reinforcing film side of the optical member to which the reinforcing film is bonded.

[0006] However, when laser processing is performed by irradiating an optical component with a reinforcing film attached from the side of the reinforcing film, a problem arises in that the processed edges of the reinforcing film become raised. Since such raised portions ultimately remain in the optical device, they can cause quality defects.

[0007] The problem of the cut surface becoming raised when laser processing the polarizing plate itself (i.e., the optical component itself) has been raised conventionally, and as a means of solving this, a method has been reported in which a laser is irradiated from the resin film side of a laminate made by laminating a specific heat-resistant resin film onto a polarizing plate (Patent Documents 4 and 5). However, in order to exhibit the effect of the specific heat-resistant resin film used in this method, a thick resin film with a total thickness of 703 μm is used, which is made by coating one side of a 700 μm thick epoxy film with acrylic urethane UV resin to form a protective layer with a thickness of 3 μm, as described in Example 1 of Patent Document 4 and Example 1 of Patent Document 5. Even if this resin film functions as a reinforcing film, it is difficult to apply to optical devices that require thinning in recent years. [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] Patent No. 6366199 [Patent Document 2] Patent No. 6375467 [Patent Document 3] Patent No. 6467551 [Patent Document 4] Japanese Patent Publication No. 2005-189530 [Patent Document 5] Japanese Patent Publication No. 2009-86675 [Overview of the Initiative] [Problems that the invention aims to solve]

[0009] In other words, the object of the present invention is to provide an optical component with a surface protective film that can suppress the protrusion of the processed edge of an optical component when laser processing the thin optical component. Furthermore, it is also to provide an optical laminate equipped with such an optical component with a surface protective film. Moreover, it is also to provide a method for manufacturing an optical device using such an optical component with a surface protective film. [Means for solving the problem]

[0010] The inventors diligently conducted research to solve the problem of bulging at the processed edges when laser processing thin optical components. As a result, they discovered that by using an optical component with a surface protection film attached to a thin optical component, and then performing laser processing and re-peeling off the surface protection film, bulging at the processed edges of the exposed optical component can be suppressed, thus completing the present invention.

[0011] [1] An optical member with a surface protective film according to an embodiment of the present invention is an optical member with a surface protective film comprising a surface protective film (I) and an optical member, wherein the surface protective film (I) comprises a substrate (Ia) and an adhesive layer (Ib), the adhesive layer (Ib) and the optical member are directly laminated, the thickness of the optical member is 400 μm or less, and the thickness of the substrate (Ia) is less than 60 μm. [2] In the optical component with a surface protective film described in [1] above, the surface hardness of the adhesive layer (Ib) at 80°C may be 3.00 MPa or less. [3] In the optical component with a surface protective film described in [1] or [2] above, the thickness of the adhesive layer (Ib) may be less than 45 μm. [4] In an optical component with a surface protective film as described in any of [1] to [3] above, the peel force of the adhesive layer (Ib) against the acrylic plate at a peel angle of 180° and a tensile speed of 300 mm / min in an environment with a temperature of 23°C and a relative humidity of 50%, may be less than 0.25 N / 25 mm. [5] In an optical member with a surface protective film as described in any of [1] to [4] above, the optical member is a reinforcing film (II), and the reinforcing film (II) may include a base material (IIa) and an adhesive layer (IIb). [6] In the optical component with a surface protective film as described in [5] above, the adhesive strength of the adhesive layer (IIb) to the polyimide film at a peel angle of 180° and a tensile speed of 300 mm / min in an environment with a temperature of 23°C and a relative humidity of 50%, may be 3N / 25mm or more. [7] An optical laminate according to an embodiment of the present invention includes an optical member with a surface protective film as described in any of [1] to [6] above. [8] A method for manufacturing an optical device according to an embodiment of the present invention is a method for manufacturing an optical device including an optical member, comprising the steps of: bonding an optical member with a surface protective film as described in [5] or [6] above to another optical member; irradiating the optical member with the surface protective film with a laser from the opposite side of the other optical member as seen from the optical member with the surface protective film to perform laser processing; and re-peeling off the surface protective film after the laser processing. [Effects of the Invention]

[0012] The optical component with a surface protective film according to an embodiment of the present invention can be suitably used in the manufacturing process of optical devices where thinning is required. When laser processing is performed using the optical component with the surface protective film, the protrusion at the processed edge of the optical component exposed after the surface protective film is peeled off is suppressed, thereby reducing the occurrence of defective products. Furthermore, an optical laminate equipped with such an optical component with a surface protective film can be provided. Moreover, a method for manufacturing an optical device using such an optical component with a surface protective film can be provided. [Brief explanation of the drawing]

[0013] [Figure 1] This is a schematic cross-sectional view showing one embodiment of an optical member with a surface protective film according to an embodiment of the present invention. [Figure 2]It is a schematic cross-sectional view showing one embodiment of the optical laminate according to the embodiment of the present invention. [Figure 3] It is a schematic explanatory view for explaining a laser-processed end portion. [Modes for Carrying Out the Invention]

[0014] Where the term "mass" appears in the present specification, it may be read as "weight" which has been conventionally and commonly used as a unit of weight, and conversely, where the term "weight" appears in the present specification, it may be read as "mass" which is commonly used as an SI system unit indicating weight.

[0015] Where the term "(meth)acrylic" appears in the present specification, it means "acrylic and / or methacrylic"; where the term "(meth)acrylate" appears, it means "acrylate and / or methacrylate"; where the term "(meth)allyl" appears, it means "allyl and / or methallyl"; and where the term "(meth)acrolein" appears, it means "acrolein and / or methacrolein".

[0016] ≪≪1. Optical Member With Surface Protective Film≫≫ The optical member with a surface protective film according to the embodiment of the present invention includes a surface protective film (I) and an optical member. As long as the optical member with a surface protective film according to the embodiment of the present invention includes the surface protective film (I) and the optical member, it may include any appropriate other constituent member within a range that does not impair the effects of the present invention. The optical member with a surface protective film according to the embodiment of the present invention typically consists of the surface protective film (I) and the optical member.

[0017] The surface protective film (I) includes a base material (Ia) and an adhesive layer (Ib).

[0018] In the optical member with a surface protective film according to the embodiment of the present invention, the adhesive layer (Ib) and the optical member are directly laminated.

[0019] As optical components, any suitable optical component can be used as long as it does not impair the effects of the present invention. Typical optical components that can better demonstrate the effects of the present invention include reinforcing films and polarizing plates.

[0020] In one embodiment of the optical component, the optical component is a reinforcing film (II), which comprises a substrate (IIa) and an adhesive layer (IIb).

[0021] Figure 1 is a schematic cross-sectional view showing one embodiment of an optical member with a surface protective film according to an embodiment of the present invention. One embodiment of the optical member 1000 with a surface protective film according to an embodiment of the present invention includes a surface protective film (I) 100 and a reinforcing film (II) 200, wherein the surface protective film (I) 100 includes a base material (Ia) 11 and an adhesive layer (Ib) 12, and the reinforcing film (II) 200 includes a base material (IIa) 21 and an adhesive layer (IIb) 22, and the adhesive layer (Ib) 12 and the base material (IIa) 21 are directly laminated together.

[0022] The total thickness of the optical member with a surface protective film according to the embodiment of the present invention is preferably 200 μm to 505 μm, more preferably 210 μm to 455 μm, even more preferably 220 μm to 405 μm, and particularly preferably 230 μm to 350 μm, in order to better exhibit the effects of the present invention. If the total thickness of the optical member with a surface protective film according to the embodiment of the present invention falls outside the above range, the effects of the present invention may not be realized. If the total thickness of the optical member with a surface protective film according to the embodiment of the present invention is too thick and falls outside the above range, it may become difficult to apply it to the manufacturing process of optical devices, for example. If the total thickness of the optical member with a surface protective film according to the embodiment of the present invention is too thin and falls outside the above range, for example, if the optical member is a reinforcing film, it may not be able to exhibit the original performance of the reinforcing film, which is to impart rigidity and impact resistance to other optical members included in the optical device.

[0023] An optical component with a surface protective film according to an embodiment of the present invention comprises a surface protective film (I) and an optical component, and can be manufactured by any suitable method without impairing the effects of the present invention, provided that the adhesive layer (Ib) and the optical component are directly laminated.

[0024] One embodiment of a method for manufacturing an optical component with a surface protective film according to an embodiment of the present invention is to prepare a surface protective film (I) and an optical component, and then bond the adhesive layer (Ib) of the surface protective film (I) to the optical component. If the optical component is a reinforcing film (II), and the reinforcing film (II) includes a substrate (IIa) and an adhesive layer (IIb), then a method is to bond the adhesive layer (Ib) of the surface protective film (I) to the substrate (IIa) which is the outermost layer of the reinforcing film (II).

[0025] ≪1-1. Surface Protection Film (I)≫ The surface protective film (I) includes a substrate (Ia) and an adhesive layer (Ib). Typically, the substrate (Ia) and the adhesive layer (Ib) are directly laminated together.

[0026] The surface protective film (I) may include any other suitable component (Ic) as long as it includes a substrate (Ia) and an adhesive layer (Ib), provided that it does not impair the effects of the present invention.

[0027] Other components (Ic) include, for example, an easy-adhesion layer, an easy-slip layer, an anti-blocking layer, an antistatic layer, an anti-reflective layer, and an oligomer-preventing layer. There may be only one type of other component (Ic), or there may be two or more types.

[0028] The thickness of the surface protective film (I) is preferably 25 μm to 105 μm, more preferably 35 μm to 95 μm, even more preferably 40 μm to 85 μm, and particularly preferably 45 μm to 70 μm, in order to better exhibit the effects of the present invention. If the thickness of the surface protective film (I) falls outside the above range, the effects of the present invention may not be exhibited. If the total thickness of the surface protective film (I) is too thick and falls outside the above range, it may become difficult to apply the optical member with the surface protective film according to the embodiment of the present invention to a thin optical device, and if laser processing is performed using the optical member with the surface protective film, it may not be possible to suppress the bulging at the processed edge of the optical member that is exposed after the surface protective film is peeled off following the laser processing. If the thickness of the surface protective film (I) is too thin and falls outside the above range, if laser processing is performed using the optical member with the surface protective film, it may not be possible to suppress the bulging at the processed edge of the optical member that is exposed after the surface protective film is peeled off following the laser processing.

[0029] <1-1-a. Substrate (Ia)> The substrate (Ia) may consist of only one layer or two or more layers. The substrate (Ia) may be stretched.

[0030] The thickness of the substrate (Ia) is preferably less than 60 μm, more preferably less than 55 μm, even more preferably less than 50 μm, particularly preferably less than 45 μm, and most preferably less than 40 μm. The lower limit of the thickness of the substrate (Ia) is that the thinner the better, but it is preferably 24 μm or more, more preferably 27 μm or more, even more preferably 30 μm or more, particularly preferably 33 μm or more, and most preferably 36 μm or more. If the thickness of the substrate (Ia) is within the above range, the effects of the present invention can be more fully realized. If the thickness of the substrate (Ia) is outside the above range, the effects of the present invention will be difficult to realize. For example, when a reinforcing film with a surface protective film is bonded to an optical member and laser processing is performed, there is a risk that the bulging at the processed edge of the reinforcing film exposed after the surface protective film is peeled off after the laser processing cannot be suppressed.

[0031] On the side of the substrate (Ia) opposite to the adhesive layer (Ib), a release treatment may be performed by adding, for example, fatty acid amides, polyethyleneimines, long-chain alkyl additives, etc., to the extent that the effects of the present invention are not impaired, or a coating layer made of any suitable release agent such as silicone-based, long-chain alkyl-based, or fluorine-based may be provided.

[0032] As the material for the base material (Ia), any suitable material can be used as long as it does not impair the effects of the present invention. Examples of such materials include plastics, paper, metal films, and nonwoven fabrics, and plastics are preferred. That is, the base material (Ia) is preferably a plastic film. The base material (Ia) may be composed of one type of material or of two or more types of materials. For example, it may be composed of two or more types of plastics.

[0033] Examples of the above-mentioned plastics include polyester resins, polyamide resins, and polyolefin resins. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyolefin resins include homopolymers of olefin monomers and copolymers of olefin monomers. Specifically, examples of polyolefin resins include homopolypropylene; propylene copolymers such as block, random, and graft types with ethylene as the copolymer component; reactor TPO; ethylene polymers such as low-density, high-density, linear low-density, and ultra-low-density polymers; ethylene copolymers such as ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-methacrylic acid copolymer, and ethylene-methyl methacrylate copolymer.

[0034] The base material (Ia) may contain any suitable additives as needed. Examples of additives that may be contained in the base material (Ia) include antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fillers, and pigments. The type, number, and amount of additives that may be contained in the base material (Ia) can be appropriately set according to the purpose. In particular, when the material of the base material (Ia) is plastic, it is preferable to contain some of the above additives for the purpose of preventing degradation, etc. From the viewpoint of improving weather resistance, antioxidants, ultraviolet absorbers, light stabilizers, and fillers are particularly preferred as additives.

[0035] Any suitable antioxidant can be used. Examples of such antioxidants include phenolic antioxidants, phosphorus-based heat stabilizers, lactone-based heat stabilizers, sulfur-based heat stabilizers, and phenol-phosphorus antioxidants. The antioxidant content is preferably 1% by weight or less, more preferably 0.5% by weight or less, and even more preferably 0.01% to 0.2% by weight, relative to the base resin of the substrate (Ia) (if the base resin forming the substrate (Ia) is a blend, then that blend is the base resin).

[0036] Any suitable UV absorber can be used as the UV absorber. Examples of such UV absorbers include benzotriazole-based UV absorbers, triazine-based UV absorbers, and benzophenone-based UV absorbers. The content of the UV absorber is preferably 2% by weight or less, more preferably 1% by weight or less, and even more preferably 0.01% to 0.5% by weight, relative to the base resin forming the substrate (Ia) (if the base resin forming the substrate (Ia) is a blend, then that blend is the base resin).

[0037] Any suitable light stabilizer can be used. Examples of such light stabilizers include hindered amine-based light stabilizers and benzoate-based light stabilizers. The content of the light stabilizer is preferably 2% by weight or less, more preferably 1% by weight or less, and even more preferably 0.01% to 0.5% by weight, relative to the base resin forming the substrate (Ia) (if the base resin forming the substrate (Ia) is a blend, then that blend is the base resin).

[0038] Any suitable filler can be used as the filler. Examples of such fillers include inorganic fillers. Specifically, examples of inorganic fillers include carbon black, titanium dioxide, and zinc oxide. The filler content is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably 0.01% to 10% by weight, relative to the base resin forming the substrate (Ia) (if the base resin forming the substrate (Ia) is a blend, then that blend is the base resin).

[0039] Furthermore, as additives, inorganic, low-molecular-weight, and high-molecular-weight antistatic agents such as surfactants, inorganic salts, polyhydric alcohols, metal compounds, and carbon are also preferred for the purpose of imparting antistatic properties. In particular, high-molecular-weight antistatic agents and carbon are preferred from the viewpoint of preventing contamination and maintaining tackiness.

[0040] <1-1-b. Adhesive layer (Ib)> The adhesive layer (Ib) may consist of only one layer or two or more layers.

[0041] The thickness of the adhesive layer (Ib) is preferably less than 45 μm, more preferably 1 μm to 40 μm, even more preferably 2 μm to 35 μm, particularly preferably 3 μm to 30 μm, and most preferably 5 μm to 25 μm. The effects of the present invention can be better realized when the thickness of the adhesive layer (Ib) is within the above range. If the thickness of the adhesive layer (Ib) is outside the above range, the effects of the present invention will be difficult to realize. For example, when laser processing is performed using an optical member with a surface protective film, it may not be possible to suppress the bulging at the processed edge of the optical member that is exposed after the surface protective film is peeled off after laser processing.

[0042] The adhesive layer (Ib) has a surface hardness at 80°C that is preferably 3.00 MPa or less, more preferably 2.00 MPa or less, even more preferably 1.00 MPa or less, particularly preferably 0.80 MPa or less, and most preferably 0.60 MPa or less. The lower limit of the above surface hardness is preferably 0.05 MPa or more, more preferably 0.10 MPa or more, even more preferably 0.15 MPa or more, and particularly preferably 0.18 MPa or more. If the surface hardness of the adhesive layer (Ib) at 80°C is within the above range, the effects of the present invention can be more fully realized. If the above surface hardness falls outside the above range, the effects of the present invention become difficult to realize, and for example, when laser processing is performed using an optical member with a surface protective film, there is a risk that the bulging at the processed edge of the optical member exposed after the surface protective film is peeled off after laser processing cannot be suppressed.

[0043] The adhesive layer (Ib) has a peel force against the acrylic sheet at a peel angle of 180 degrees and a tensile speed of 300 mm / min in an environment of 23°C and 50% relative humidity, preferably less than 0.25 N / 25 mm, more preferably less than 0.23 N / 25 mm, even more preferably less than 0.22 N / 25 mm, particularly preferably less than 0.21 N / 25 mm, and most preferably less than 0.20 N / 25 mm. The lower limit of the above peel force against the acrylic sheet is preferably 0.01 N / 25 mm or more, more preferably 0.02 N / 25 mm or more, even more preferably 0.03 N / 25 mm or more, and particularly preferably 0.04 N / 25 mm or more. If the above peel force against the acrylic sheet is within the above range, the surface protective film can be easily re-peeled off the optical member with the surface protective film according to the embodiment of the present invention.

[0044] The adhesive constituting the adhesive layer (Ib) can be any suitable adhesive, as long as it does not impair the effects of the present invention. Preferably, the adhesive constituting the adhesive layer is an acrylic adhesive, as this allows for better expression of the effects of the present invention.

[0045] Acrylic adhesives are formed from acrylic adhesive compositions.

[0046] Acrylic adhesives can thus be defined as those formed from acrylic adhesive compositions. This is because acrylic adhesives are formed when acrylic adhesive compositions undergo crosslinking reactions such as heating or ultraviolet irradiation, making it impossible and impractical to directly identify acrylic adhesives by their structure. Therefore, the definition "formed from acrylic adhesive compositions" appropriately identifies acrylic adhesives as a "substance."

[0047] The adhesive layer (Ib) can be formed by any suitable method. Such methods include, for example, applying an adhesive composition that forms the adhesive constituting the adhesive layer onto a substrate (Ia), heating and drying as necessary, and curing as necessary to form the adhesive layer (Ib) on the substrate (Ia); or applying an adhesive composition that forms the adhesive constituting the adhesive layer (Ib) onto any suitable film such as a release liner, heating and drying as necessary, and curing as necessary to form the adhesive layer (Ib) on the film, and then bonding and transferring the substrate (Ia) onto the adhesive layer (Ib) to form the adhesive layer (Ib) on the substrate (Ia).

[0048] Any suitable means can be used to apply the adhesive composition, as long as it does not impair the effects of the present invention. Examples of such application methods include the roll coating method, gravure roll coating method, reverse roll coating method, kiss roll coating method, dip roll coating method, bar coating method, roll brush coating method, spray coating method, knife coating method, air knife coating method, comma coating method, direct coating method, and die coating method.

[0049] The heating and drying of the adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. Examples of such heating and drying methods include heating to 60°C to 180°C, or performing an aging treatment at a temperature of approximately room temperature.

[0050] The curing of the adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. Examples of such curing means include heat, ultraviolet irradiation, laser irradiation, alpha irradiation, beta irradiation, gamma irradiation, X-ray irradiation, and electron beam irradiation.

[0051] The acrylic adhesive composition preferably contains an acrylic polymer (A) in that it can better exhibit the effects of the present invention.

[0052] Acrylic polymer (A) can be referred to as a so-called base polymer in the field of acrylic adhesives. Acrylic polymer (A) may consist of only one type or two or more types.

[0053] The content of acrylic polymer (A) in the acrylic adhesive composition is preferably 60% to 99.9% by weight, more preferably 65% ​​to 99.9% by weight, even more preferably 70% to 99.9% by weight, particularly preferably 75% to 99.9% by weight, and most preferably 80% to 99.9% by weight, based on solid content.

[0054] As the acrylic polymer (A), any suitable acrylic polymer can be used, as long as it does not impair the effects of the present invention.

[0055] The weight-average molecular weight of the acrylic polymer (A) is preferably 300,000 to 2,500,000, more preferably 350,000 to 2,000,000, even more preferably 400,000 to 1,500,000, and particularly preferably 450,000 to 1,000,000, in order to better exhibit the effects of the present invention.

[0056] The acrylic polymer (A) is preferably an acrylic polymer formed by polymerization from a composition (M) which contains an alkyl (meth)acrylate (component a) in which the alkyl group of the alkyl ester portion has 4 to 12 carbon atoms, and at least one (component b) selected from the group consisting of (meth)acrylate esters having an OH group and (meth)acrylic acid. Component a and component b may each be independent of one type or two or more types.

[0057] The number of carbon atoms in the alkyl group of the alkyl ester portion of the alkyl ester portion of the alkyl (meth)acrylate (component a) is preferably 4 to 10, more preferably 4 to 9, and even more preferably 4 to 8, in order to better express the effects of the present invention.

[0058] Examples of alkyl (meth)acrylate esters having 4 to 12 carbon atoms in the alkyl group of the alkyl ester portion include n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Among these, n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred in terms of being able to better exhibit the effects of the present invention, and more preferably n-butyl acrylate and 2-ethylhexyl acrylate.

[0059] The content of the alkyl ester (meth)acrylate (component a), in which the alkyl group of the alkyl ester portion has 4 to 12 carbon atoms, is preferably 30% by weight or more, more preferably 50% to 99% by weight, even more preferably 70% to 98% by weight, particularly preferably 80% to 98% by weight, and most preferably 90% to 98% by weight, relative to the total amount (100% by weight) of the monomer components constituting the acrylic polymer (A), in order to better express the effects of the present invention.

[0060] Examples of (meth)acrylic acid esters having an OH group include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate. Among these, hydroxyethyl (meth)acrylate is preferred, and more preferably, hydroxyethyl acrylate, in terms of being able to better express the effects of the present invention.

[0061] As the (meth)acrylic acid, acrylic acid is preferred in that it can better exhibit the effects of the present invention.

[0062] The content of at least one component (b) selected from the group consisting of (meth)acrylic acid esters having an OH group and (meth)acrylic acid is preferably 1% by weight or more, more preferably 1% to 30% by weight, even more preferably 2% to 20% by weight, and particularly preferably 3% to 10% by weight, relative to the total amount (100% by weight) of monomer components constituting the acrylic polymer (A), in order to better express the effects of the present invention.

[0063] The total amount of component a and component b relative to the total amount (100% by weight) of monomer components constituting the acrylic polymer (A) is preferably 50% to 100% by weight, more preferably 70% to 100% by weight, even more preferably 90% to 100% by weight, particularly preferably 95% to 100% by weight, and most preferably 98% to 100% by weight, in order to better exhibit the effects of the present invention.

[0064] Composition (M) may contain copolymerizable monomers other than components a and b. The copolymerizable monomer may be one type or two or more types.

[0065] The content of copolymerizable monomers other than components a and b relative to the total amount (100% by weight) of monomer components constituting the acrylic polymer (A) is preferably 50% by weight or less, more preferably 30% by weight or less, even more preferably 10% by weight or less, particularly preferably 5% by weight or less, and most preferably 2% by weight or less, in order to better exhibit the effects of the present invention.

[0066] Examples of such copolymerizable monomers include carboxyl group-containing monomers such as itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and their acid anhydrides (e.g., acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride) (excluding (meth)acrylic acid); (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide. ) Amide group-containing monomers such as acrylamide; amino group-containing monomers such as (meth)aminoethyl acrylate, (meth)dimethylaminoethyl acrylate, and (meth)t-butylaminoethyl acrylate; epoxy group-containing monomers such as (meth)glycidyl acrylate and (meth)methylglycidyl acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; N-vinyl-2-pyrrolidone, (meth)acryloylmorpholine, N-vinylpiperidone, N-vinylpiperazine, N-vinylpyrrole, N-vinyl Examples include heterocyclic vinyl monomers such as imidazole, vinylpyridine, vinylpyrimidine, and vinyloxazole; sulfonic acid group-containing monomers such as sodium vinylsulfonate; phosphate group-containing monomers such as 2-hydroxyethyl acryloyl phosphate; imide group-containing monomers such as cyclohexyl maleimide and isopropyl maleimide; isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate; (meth)acrylic acid esters having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid esters having aromatic hydrocarbon groups such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins and dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ethers; and vinyl chloride.

[0067] Polyfunctional monomers can also be used as copolymerizable monomers. A polyfunctional monomer is a monomer having two or more ethylenically unsaturated groups in one molecule. Any suitable ethylenically unsaturated group can be used as the ethylenically unsaturated group, as long as it does not impair the effects of the present invention. Examples of such ethylenically unsaturated groups include radical polymerizable functional groups such as vinyl groups, propenyl groups, isopropenyl groups, vinyl ether groups (vinyloxy groups), and allyl ether groups (allyloxy groups). Examples of polyfunctional monomers include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl(meth)acrylate, vinyl(meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. Such polyfunctional monomers may be present individually or in combination of two or more types.

[0068] As copolymerizable monomers, alkoxyalkyl (meth)acrylates may also be used. Examples of alkoxyalkyl (meth)acrylates include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. There may be only one alkoxyalkyl (meth)acrylate or two or more.

[0069] Composition (M) may contain any other suitable components, as long as they do not impair the effects of the present invention. Examples of such other components include polymerization initiators, chain transfer agents, and solvents. The content of these other components may be any suitable amount, as long as they do not impair the effects of the present invention.

[0070] Depending on the type of polymerization reaction, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator (photoinitiator). There may be only one polymerization initiator or two or more.

[0071] A thermal polymerization initiator can preferably be used when obtaining an acrylic polymer (A) by solution polymerization. Examples of such thermal polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid)dimethyl, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, and 2,2'-azobis[2-(5-methyl-2-imidazoline-2-yl)pro Azo initiators such as pan-dihydrochloride, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N,N'-dimethylene isobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate, and di(2-ethylhexyl) peroxydicarbonate. Examples include peroxide initiators such as di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butylperoxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butylhydroperoxide, and hydrogen peroxide; redox initiators combining peroxides with reducing agents, such as combinations of persulfates and sodium bisulfite, and combinations of peroxides and sodium ascorbate; substituted ethane initiators such as phenyl-substituted ethane; and aromatic carbonyl compounds.

[0072] Photopolymerization initiators can preferably be used when obtaining an acrylic polymer (A) by active energy ray polymerization. Examples of photopolymerization initiators include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators.

[0073] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. An example of an aromatic sulfonyl chloride-based photopolymerization initiator is 2-naphthalenesulfonyl chloride. Examples of photoactive oxime-based photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin-based photopolymerization initiators include benzoin. Examples of benzyl-based photopolymerization initiators include benzyl. Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenyl ketone. Examples of ketal-based photopolymerization initiators include benzyldimethylketal. Examples of thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.

[0074] The amount of polymerization initiator used can be set to any appropriate amount, as long as it does not impair the effects of the present invention.

[0075] The acrylic adhesive composition may contain a crosslinking agent. By using a crosslinking agent, the cohesive force of the acrylic adhesive can be improved, and the effects of the present invention can be further exhibited. There may be only one type of crosslinking agent, or there may be two or more types.

[0076] Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, silicone-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, silane-based crosslinking agents, alkyl etherified melamine-based crosslinking agents, metal chelate-based crosslinking agents, and peroxides. Preferably, at least one isocyanate-based crosslinking agent selected from the group consisting of isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and peroxides, as this can better express the effects of the present invention.

[0077] Isocyanate-based crosslinking agents can be compounds having two or more isocyanate groups (including isocyanate-regenerating polar groups in which isocyanate groups are temporarily protected by a blocking agent or quantification, etc.) in one molecule. Examples of isocyanate-based crosslinking agents include aromatic isocyanates such as tolylene diisocyanate and xylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate.

[0078] Examples of isocyanate-based crosslinking agents include: lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, and polymethylene polyphenyl isocyanate; trimethylolpropane / tolylene diisocyanate trimer adduct (e.g., manufactured by Mitsui Chemicals, trade name: D-101E), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate HL), and isocyanurate derivatives of hexamethylene diisocyanate (e.g., manufactured by Tosoh Corporation) Examples include isocyanate adducts such as (product name: Coronate HX); trimethylolpropane adducts of xylylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D110N), trimethylolpropane adducts of xylylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D120N), trimethylolpropane adducts of isophorone diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D140N), trimethylolpropane adducts of hexamethylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D160N); polyether polyisocyanates, polyester polyisocyanates, and adducts thereof with various polyols; and polyfunctionalized polyisocyanates with isocyanurate bonds, biuret bonds, allophanate bonds, etc. Among these, aromatic isocyanates and alicyclic isocyanates are preferred because they can achieve a good balance between deformability and cohesiveness.

[0079] As epoxy crosslinking agents, polyfunctional epoxy compounds having two or more epoxy groups in one molecule can be used. Examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylenediline, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitol polyglycidyl ether. Examples of epoxy crosslinking agents include tel, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate ester, diglycidyl o-phthalate ester, triglycidyl-tris(2-hydroxyethyl) isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of commercially available epoxy crosslinking agents include the trade names "Tetrad C" and "Tetrad X" manufactured by Mitsubishi Gas Chemical Company.

[0080] Examples of peroxides include dibenzoyl peroxide, dicumyl peroxide, di-t-butyl peroxide, di-t-butylperoxy-3,3,5-trimethylcyclohexane, t-butyl hydroperoxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexine-3, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-mono(t-butylperoxy)hexane, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, and t-butylperoxy Examples include neodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, t-butyl peroxyisobutyrate, 1,1-di(t-hexyl peroxy)cyclohexane, 1,1-di(t-butyl peroxy)cyclohexane, t-butyl peroxy-2-ethylhexyl carbonate, t-amyl peroxyisopropyl carbonate, 3,5,5-trimethylhexanoyl peroxide, t-butyl peroxy-2-hexanoate, t-butyl peroxypivalate, and t-hexyl peroxypivalate. Examples of commercially available peroxides include the "Nipper BMT" series and "Nipper BW" series manufactured by Nippon Oil & Fats Co., Ltd.

[0081] The amount of crosslinking agent in the acrylic adhesive composition can be any appropriate amount, as long as it does not impair the effects of the present invention. For example, in terms of better exhibiting the effects of the present invention, the amount is preferably 0.01 to 20 parts by weight, more preferably 0.01 to 18 parts by weight, even more preferably 0.01 to 15 parts by weight, and particularly preferably 0.05 to 10 parts by weight, relative to the solid content (100 parts by weight) of the acrylic polymer (A).

[0082] The acrylic adhesive composition may contain any other suitable components as long as they do not impair the effects of the present invention. Examples of such other components include polymer components other than the acrylic polymer (A), crosslinking accelerators, crosslinking catalysts, silane coupling agents, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), anti-aging agents, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foils, ultraviolet absorbers, antioxidants, light stabilizers, nucleating agents, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, conductive agents, stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, solvents, and catalysts.

[0083] ≪1-2. Optical Components≫ As optical components, any suitable optical component can be used as long as it does not impair the effects of the present invention. Typical optical components that can better demonstrate the effects of the present invention include reinforcing films and polarizing plates.

[0084] The thickness of the optical component is 400 μm or less, more preferably 5 μm to 350 μm, more preferably 10 μm to 300 μm, even more preferably 15 μm to 280 μm, particularly preferably 20 μm to 260 μm, and most preferably 25 μm to 250 μm, in order to better exhibit the effects of the present invention. If the thickness of the optical component is too thick outside the above range, it may become difficult to apply the optical component with a surface protective film according to the embodiment of the present invention to a thin optical device. If the thickness of the optical component is too thin outside the above range, for example, if the optical component is a reinforcing film, it may not be able to exhibit the original performance of the reinforcing film, which is to impart rigidity and impact resistance to other optical components included in the optical device.

[0085] One embodiment of the optical component is a reinforcing film (II), which includes a substrate (IIa) and an adhesive layer (IIb). The reinforcing film (II), which is one embodiment of the optical component, will be described below.

[0086] The reinforcing film (II) includes a substrate (IIa) and an adhesive layer (IIb). In one embodiment, the substrate (IIa) and the adhesive layer (IIb) are directly laminated together.

[0087] The reinforcing film (II) may include any other suitable component (IIc) as long as it includes a base material (IIa) and an adhesive layer (IIb), provided that it does not impair the effects of the present invention.

[0088] Other components (IIc) include, for example, an antistatic layer, an anti-reflective layer, an anti-glare layer, and a hard coat layer. There may be only one type of other component (IIc) or two or more types.

[0089] When the optical component is a reinforcing film (II), the thickness of the reinforcing film (II) is preferably 150 μm or less, more preferably 5 μm to 140 μm, more preferably 10 μm to 130 μm, even more preferably 15 μm to 120 μm, particularly preferably 20 μm to 110 μm, and most preferably 25 μm to 100 μm, in order to better exhibit the effects of the present invention. If the thickness of the reinforcing film (II) is too thick outside the above range, it may become difficult to apply the optical component with the surface protective film according to the embodiment of the present invention to a thin optical device. If the thickness of the reinforcing film (II) is too thin outside the above range, it may become impossible to exhibit the inherent performance of the reinforcing film, such as imparting rigidity and impact resistance to other optical components included in the optical device.

[0090] <1-2-a. Base material (IIa)> The base material (IIa) may consist of only one layer or two or more layers. The base material (IIa) may also be stretched.

[0091] The thickness of the substrate (IIa) is preferably 4 μm to 100 μm, more preferably 10 μm to 95 μm, even more preferably 15 μm to 90 μm, particularly preferably 20 μm to 85 μm, and most preferably 25 μm to 80 μm, in order to better exhibit the effects of the present invention. If the thickness of the substrate (IIa) is too thick outside the above range, it may become difficult to apply the optical component with the surface protective film according to the embodiment of the present invention to a thin optical device. If the thickness of the substrate (IIa) is too thin outside the above range, it may become impossible to exhibit the inherent performance of the reinforcing film, such as providing rigidity and impact resistance to other optical components included in the optical device.

[0092] As the material for the base material (IIa), any suitable material can be used as long as it does not impair the effects of the present invention. Examples of such materials include, preferably, plastics, nonwoven fabrics, paper, metal foils, woven fabrics, rubber, and foams, and are preferably plastics. That is, the base material (IIa) is preferably a plastic film. The base material (IIa) may be composed of one type of material or of two or more types of materials. For example, it may be composed of two or more types of plastics.

[0093] Examples of the above-mentioned plastics include acrylic resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polymethyl methacrylate (PMMA), as well as polycarbonate, triacetylcellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), fully aromatic polyamide (aramid), polyimide (PI), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluoropolymers, polyetheretherketone (PEEK), and cyclic olefin polymers.

[0094] Examples of the above-mentioned nonwoven fabrics include nonwoven fabrics made from heat-resistant natural fibers such as Manila hemp; and synthetic resin nonwoven fabrics such as polypropylene resin nonwoven fabric, polyethylene resin nonwoven fabric, and ester-based resin nonwoven fabric.

[0095] The substrate (IIa) preferably has a total light transmittance of 90% or more, more preferably 91% or more, even more preferably 92% or more, and particularly preferably 93% or more. If the total light transmittance of the substrate (IIa) is within the above range, there is an advantage that the inspectability is less likely to deteriorate when inspecting optical or electronic components through the reinforcing film.

[0096] The substrate (IIa) may be surface-treated. Examples of surface treatments include corona treatment, plasma treatment, chromic acid treatment, ozone exposure, flame exposure, high-voltage electric shock exposure, ionization radiation treatment, and coating with a primer.

[0097] Examples of organic coating materials include those described in Plastic Hard Coat Materials II (CMC Publishing, (2004)). Preferably, such organic coating materials are urethane polymers, and more preferably, polyacrylic urethane, polyester urethane, or precursors thereof. This is because they are easy to coat onto the substrate layer A1, and a wide variety of types are available industrially at low cost. Examples of such urethane polymers include polymers consisting of a reaction mixture of isocyanate monomer and alcoholic hydroxyl group-containing monomer (e.g., hydroxyl group-containing acrylic compound or hydroxyl group-containing ester compound). The organic coating material may contain optional additives such as chain extenders like polyamines, antioxidants, and oxidation stabilizers.

[0098] The base material (IIa) may contain any suitable additives as needed. Examples of additives that can be contained in the base material (IIa) include antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fillers, and pigments. The type, number, and amount of additives that can be contained in the base material (IIa) can be appropriately set according to the purpose. In particular, when the material of the base material (IIa) is plastic, it is preferable to contain some of the above additives for the purpose of preventing deterioration, etc. From the viewpoint of improving weather resistance, antioxidants, ultraviolet absorbers, light stabilizers, and fillers are particularly preferred as additives. Furthermore, since it is a preferred embodiment for the base material (IIa) to have an antistatic effect, it is also a preferred embodiment to include an antistatic agent.

[0099] <1-2-b. Adhesive layer (IIb)> The adhesive layer (IIb) may consist of only one layer or two or more layers.

[0100] The thickness of the adhesive layer (IIb) is preferably 1 μm to 50 μm, more preferably 2 μm to 40 μm, even more preferably 4 μm to 35 μm, particularly preferably 5 μm to 30 μm, and most preferably 7 μm to 25 μm. The effects of the present invention can be better realized when the thickness of the adhesive layer (IIb) is within the above range. If the thickness of the adhesive layer (IIb) is too thick and outside the above range, it may become difficult to apply the optical component with the surface protective film according to the embodiment of the present invention to a thin optical device. If the thickness of the adhesive layer (IIb) is too thin and outside the above range, it may not be able to realize the original performance of the reinforcing film, such as providing rigidity and impact resistance to other optical components included in the optical device.

[0101] The adhesive strength of the adhesive layer (IIb) to the polyimide film at a peel angle of 180° and a tensile speed of 300 mm / min in an environment of 23°C and 50% relative humidity is preferably 3N / 25mm or more, more preferably 4N / 25mm or more, even more preferably 5N / 25mm or more, and particularly preferably 6N / 25mm or more. If the above adhesive strength to the polyimide film is within the above range, the reinforcing film portion of the optical component with a surface protective film according to the embodiment of the present invention can be firmly and reliably permanently bonded to the adherend (typically the optical component).

[0102] The adhesive constituting the adhesive layer (IIb) can be any suitable adhesive, as long as it does not impair the effects of the present invention. Examples of such adhesives include the adhesive described in Japanese Patent Publication No. 6375467 and the photocurable adhesive described in Japanese Patent Publication No. 6467551.

[0103] A typical example of the adhesive layer (IIb) is an acrylic adhesive.

[0104] Acrylic adhesives are formed from acrylic adhesive compositions.

[0105] Acrylic adhesives can thus be defined as those formed from acrylic adhesive compositions. This is because acrylic adhesives are formed when acrylic adhesive compositions undergo crosslinking reactions such as heating or ultraviolet irradiation, making it impossible and impractical to directly identify acrylic adhesives by their structure. Therefore, the definition "formed from acrylic adhesive compositions" appropriately identifies acrylic adhesives as a "substance."

[0106] The adhesive layer (IIb) can be formed by any suitable method. Such methods include, for example, applying an adhesive composition that forms the adhesive constituting the adhesive layer onto a substrate (IIa), heating and drying as necessary, and curing as necessary to form the adhesive layer (IIb) on the substrate (IIa); or applying an adhesive composition that forms the adhesive constituting the adhesive layer (IIb) onto any suitable film such as a release liner, heating and drying as necessary, and curing as necessary to form the adhesive layer (IIb) on the film, and then forming the adhesive layer (IIb) on the substrate (IIa) by laminating and transferring the substrate (IIa) onto the adhesive layer (IIb).

[0107] Any suitable means can be used to apply the adhesive composition, as long as it does not impair the effects of the present invention. Examples of such application methods include the roll coating method, gravure roll coating method, reverse roll coating method, kiss roll coating method, dip roll coating method, bar coating method, roll brush coating method, spray coating method, knife coating method, air knife coating method, comma coating method, direct coating method, and die coating method.

[0108] The heating and drying of the adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. Examples of such heating and drying methods include heating to 60°C to 180°C, or performing an aging treatment at a temperature of approximately room temperature.

[0109] The curing of the adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. Examples of such curing means include heat, ultraviolet irradiation, laser irradiation, alpha irradiation, beta irradiation, gamma irradiation, X-ray irradiation, and electron beam irradiation.

[0110] The acrylic adhesive composition preferably contains an acrylic polymer (B) in that it can better exhibit the effects of the present invention.

[0111] Acrylic polymer (B) can be referred to as a so-called base polymer in the field of acrylic adhesives. Acrylic polymer (B) may consist of only one type or two or more types.

[0112] The content of acrylic polymer (B) in the acrylic adhesive composition is preferably 60% to 99.9% by weight, more preferably 65% ​​to 99.9% by weight, even more preferably 70% to 99.9% by weight, particularly preferably 75% to 99.9% by weight, and most preferably 80% to 99.9% by weight, based on solid content.

[0113] As the acrylic polymer (B), any suitable acrylic polymer can be used, as long as it does not impair the effects of the present invention.

[0114] The weight-average molecular weight of the acrylic polymer (B) is preferably 200,000 to 2,500,000, more preferably 300,000 to 1,800,000, even more preferably 400,000 to 1,500,000, and particularly preferably 500,000 to 1,200,000, in order to better exhibit the effects of the present invention.

[0115] The acrylic polymer (B) is preferably formed from monomer components that include an alkyl (meth)acrylate having a linear or branched alkyl group and a polar group-containing monomer.

[0116] The alkyl (meth)acrylate ester having a linear or branched alkyl group may be one type or two or more types.

[0117] Examples of alkyl (meth)acrylate esters having linear or branched alkyl groups include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, Examples of alkyl (meth)acrylates having a linear or branched alkyl group having 1 to 20 carbon atoms include nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. The alkyl (meth)acrylate having a linear or branched alkyl group is preferably at least one selected from methyl (meth)acrylate and 2-ethylhexyl (meth)acrylate, in terms of better exhibiting the effects of the present invention.

[0118] The polar group-containing monomer may be one type or two or more types.

[0119] Examples of polar group-containing monomers include hydroxyl group-containing monomers, nitrogen-containing monomers, epoxy group-containing monomers, sulfonic acid group-containing monomers, phosphate group-containing monomers, and carboxyl group-containing monomers. Preferably, the polar group-containing monomer is at least one selected from hydroxyl group-containing monomers and nitrogen-containing monomers, as this allows for better expression of the effects of the present invention.

[0120] The polar group-containing monomer preferably contains a hydroxyl group-containing monomer, as this allows the effects of the present invention to be more fully expressed.

[0121] Examples of monomers containing hydroxyl groups include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, vinyl alcohol, and allyl alcohol. Among the monomers containing hydroxyl groups, 2-hydroxyethyl (meth)acrylate is preferred in that it can more effectively exhibit the effects of the present invention.

[0122] Examples of nitrogen-containing monomers include amide group-containing monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide; monomers having a nitrogen-containing heterocyclic ring and an N-vinyl group (nitrogen-containing heterocyclic vinyl monomers) (e.g., N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, etc.) and nitrogen Examples include nitrogen-containing heterocyclic monomers having heterocyclic and (meth)acryloyl groups (nitrogen-containing heterocyclic (meth)acrylic monomers) (e.g., (meth)acryloylmorpholine); amino group-containing monomers such as (meth)aminoethyl acrylate, (meth)dimethylaminoethyl acrylate, and (meth)t-butylaminoethyl acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; imide group-containing monomers such as cyclohexylmaleimide and isopropylmaleimide; and isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate. As a nitrogen-containing monomer, N-vinyl-2-pyrrolidone is preferred in terms of being able to better exhibit the effects of the present invention.

[0123] Examples of epoxy group-containing monomers include glycidyl (meth)acrylate and methylglycidyl (meth)acrylate.

[0124] Examples of monomers containing sulfonic acid groups include sodium vinylsulfonate.

[0125] Examples of phosphate group-containing monomers include 2-hydroxyethyl acryloyl phosphate.

[0126] Examples of carboxyl group-containing monomers include (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and their acid anhydrides (for example, acid anhydride-containing monomers such as maleic anhydride and itaconic anhydride).

[0127] The monomer component may contain other copolymerizable monomers. These other copolymerizable monomers may be one or more. Examples of other copolymerizable monomers include polyfunctional monomers. Examples of polyfunctional monomers include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl(meth)acrylate, vinyl(meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate.

[0128] Other copolymerizable monomers besides polyfunctional monomers include, for example, (meth)acrylic acid esters having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid esters having aromatic hydrocarbon groups such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins or dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ethers; and vinyl chloride.

[0129] In the total amount of monomer components forming the acrylic polymer (B), the content of alkyl (meth)acrylate having a linear or branched alkyl group is preferably 50% to 95% by weight, more preferably 55% to 90% by weight, even more preferably 60% to 85% by weight, and particularly preferably 65% ​​to 80% by weight, in order to better exhibit the effects of the present invention.

[0130] In the total amount of monomer components forming the acrylic polymer (B), the content of polar group-containing monomers is preferably 5% to 50% by weight, more preferably 10% to 45% by weight, even more preferably 15% to 40% by weight, and particularly preferably 20% to 35% by weight, in order to better exhibit the effects of the present invention.

[0131] When a hydroxyl group-containing monomer is essential as the polar group-containing monomer, the content of the hydroxyl group-containing monomer in the total amount of monomer components forming the acrylic polymer (B) is preferably 5% to 25% by weight, more preferably 7% to 22% by weight, even more preferably 9% to 20% by weight, and particularly preferably 10% to 18% by weight, in order to better express the effects of the present invention.

[0132] As polar group-containing monomers, it is preferable not to use carboxyl group-containing monomers, or to use them in small amounts. Specifically, the content of carboxyl group-containing monomers in the total amount of monomer components forming the acrylic polymer (B) is preferably 0% to 5% by weight, more preferably 0% to 3% by weight, even more preferably 0% to 2% by weight, and particularly preferably 0% to 0.5% by weight.

[0133] Acrylic polymer (B) is obtained by polymerizing monomer components using any suitable polymerization method, provided that the effects of the present invention are not impaired. Examples of polymerization methods for obtaining acrylic polymer (B) include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization by active energy ray irradiation (active energy ray polymerization). Among these, solution polymerization and active energy ray polymerization are preferred in terms of productivity.

[0134] Examples of solvents used when employing a solution polymerization method include organic solvents such as esters like ethyl acetate and n-butyl acetate; aromatic hydrocarbons like toluene and benzene; aliphatic hydrocarbons like n-hexane and n-heptane; alicyclic hydrocarbons like cyclohexane and methylcyclohexane; and ketones like methyl ethyl ketone and methyl isobutyl ketone. The solvent may be one type or two or more types.

[0135] When polymerization of monomer components, polymerization initiators such as thermal polymerization initiators and photopolymerization initiators (photoinitiators) are preferably used, depending on the type of polymerization reaction. There may be only one polymerization initiator or two or more.

[0136] Regarding polymerization initiators, the explanation of polymerization initiators in section <1-1-b. Adhesive layer (Ib)> can be directly applied.

[0137] The acrylic adhesive composition preferably contains a crosslinking agent. By using a crosslinking agent, it is possible to provide an acrylic adhesive that has sufficient adhesive strength and low distortion at high temperatures. The crosslinking agent may be one type or two or more types.

[0138] The crosslinking agent may be one type or two or more types.

[0139] The amount of crosslinking agent in the acrylic adhesive composition can be any appropriate amount, as long as it does not impair the effects of the present invention. For example, in terms of better exhibiting the effects of the present invention, the amount is preferably 0.1 to 30 parts by weight, more preferably 0.3 to 25 parts by weight, even more preferably 0.5 to 20 parts by weight, particularly preferably 0.7 to 15 parts by weight, and most preferably 1 to 10 parts by weight, relative to the solid content (100 parts by weight) of the acrylic polymer (B). If the amount of crosslinking agent in the acrylic adhesive composition is within the above range relative to the solid content (100 parts by weight) of the acrylic polymer (B), an acrylic adhesive with more sufficient adhesive strength and less distortion at high temperatures can be provided.

[0140] Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, silicone-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, silane-based crosslinking agents, alkyl etherified melamine-based crosslinking agents, metal chelate-based crosslinking agents, and peroxides. Preferably, at least one isocyanate-based crosslinking agent selected from the group consisting of isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and peroxides, as this can better express the effects of the present invention.

[0141] For specific explanations of isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and peroxides, the explanation regarding polymerization initiators in section <1-1-b. Adhesive layer (Ib)> can be directly applied.

[0142] The acrylic adhesive composition may contain any other suitable components, as long as they do not impair the effects of the present invention. For example, the description of other components in section <1-1-b. Adhesive layer (Ib)> can be directly applied.

[0143] ≪≪2. Optical laminate≫≫ An optical laminate according to an embodiment of the present invention includes an optical component with a surface protective film according to an embodiment of the present invention. More preferably, an optical laminate according to an embodiment of the present invention includes an optical component with a surface protective film according to an embodiment of the present invention and other optical components.

[0144] Figure 2 shows one embodiment of the optical laminate of the present invention, in which the optical laminate 3000 includes an optical member 1000 with a surface protective film and other optical members 2000, the optical member 1000 with a surface protective film includes a surface protective film (I) 100 and a reinforcing film (II) 200.

[0145] The optical laminate according to an embodiment of the present invention may include any other suitable layer, provided that it does not impair the effects of the present invention, as long as it includes an optical member with a surface protective film according to an embodiment of the present invention.

[0146] Other layers include, for example, glass, displays, imaging devices, lenses, and (half) mirrors.

[0147] The total thickness of the optical laminate according to the embodiments of the present invention can be any appropriate thickness depending on the type of other optical components. Typically, the total thickness of the optical laminate according to the embodiments of the present invention is preferably 115 μm to 650 μm, more preferably 120 μm to 600 μm, even more preferably 125 μm to 550 μm, and particularly preferably 130 μm to 500 μm.

[0148] Other optical components include, for example, polarizers, polyimide films, waveplates, phase difference plates, optical compensation films, brightness enhancement films, light diffusion sheets, and reflective sheets.

[0149] The thickness of other optical components can be any appropriate thickness depending on their type. Typically, the thickness of other optical components is preferably 5 μm to 400 μm, more preferably 10 μm to 350 μm, even more preferably 15 μm to 300 μm, and particularly preferably The size is between 20 μm and 250 μm.

[0150] ≪≪3. Method for Manufacturing Optical Devices≫≫ A method for manufacturing an optical device according to an embodiment of the present invention is a method for manufacturing an optical device including an optical component, and uses an optical component with a surface protective film according to an embodiment of the present invention and other optical components.

[0151] For other optical components, the explanations regarding other optical components in section 2. Optical Laminates can be directly applied.

[0152] A method for manufacturing an optical device according to an embodiment of the present invention includes the steps of: bonding an optical member with a surface protective film according to an embodiment of the present invention to another optical member (hereinafter referred to as step I); performing laser processing by irradiating the optical member with the surface protective film with a laser from the opposite side of the other optical member as seen from the optical member with the surface protective film (hereinafter referred to as step II); and re-peeling off the surface protective film after the laser processing (hereinafter referred to as step III).

[0153] In step I, the optical member side of the optical member with the surface protective film according to an embodiment of the present invention is bonded to another optical member to which the optical member with the surface protective film is to be bonded. This results in an optical laminate in which, for example, the surface protective film, the optical member, and the other optical member are laminated in this order.

[0154] Subsequently, in step II, laser processing is performed by irradiating the optical laminate obtained in step I with a laser from the surface protection film side. In this case, by irradiating with a laser, a cut surface is created in the optical laminate, and the optical component with the surface protection film (a laminate of the surface protection film and the optical component) is partially removed from the optical laminate. As a result, a laminate is obtained in which the optical component with the surface protection film is partially bonded to other optical components.

[0155] Subsequently, in step III, the surface protective film is re-peeled off from the laminate obtained in step II, which has the optical component partially mounted on the other optical components. As a result, an optical device is obtained in which the optical component is partially bonded to the other optical components.

[0156] According to the method for manufacturing an optical device according to an embodiment of the present invention, the processed end of the optical component of the obtained optical device does not show any bulges, as can be seen in conventional processing methods, that is, in processing methods in which a laser is irradiated from the side of an optical component to which a reinforcing film is bonded, and laser processing is performed.

[0157] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way to these examples. The test and evaluation methods in the examples are as follows. When "parts" is written, it means "parts by weight" unless otherwise specified, and when "%" is written, it means "percent by weight" unless otherwise specified.

[0158] <Measurement of weight-average molecular weight> The weight-average molecular weight was measured by gel permeation chromatography (GPC). Specifically, the GPC measuring device was the "HLC-8120GPC" (manufactured by Tosoh Corporation), and measurements were taken under the following conditions. The weight-average molecular weight was then calculated based on the standard polystyrene equivalent. (Molecular weight measurement conditions) • Sample concentration: Approximately 2.0 g / L (tetrahydrofuran solution) • Sample injection volume: 20 μL • Column: Product name "TSKgel, SuperAWM-H + superAW4000 + superAW2500" (manufactured by Tosoh Corporation) • Column size: 6.0mm I.D. x 150mm each • Eluent: Tetrahydrofuran (THF) ·Flow rate: 0.4mL / min • Detector: Differential refractometer (RI) Column temperature (measurement temperature): 40°C

[0159] <Surface hardness of the adhesive layer of the surface protection film> The surface hardness of the surface protection films obtained in the examples and comparative examples was measured. The release liner protecting the adhesive surface was peeled off, and the surface hardness was measured using a nanoindenter (Hysitron Inc.). Using a Triboindenter, indent the adhesive layer surface to a depth of 1 μm. By pressing it in, the maximum load (Pmax) [GPa / mm²] was measured using the nanoindenter described above. 2 We obtained ]. This can be expressed as formula: Surface hardness [GPa] = Pmax / A The surface hardness was calculated by substituting the values ​​into the formula. The measurement conditions are as follows. In the above formula, A is the contact projected area of ​​the indenter [mm²]. 2 ] (Measurement conditions) Indenter approach speed: 200 nm / s Maximum displacement: 1 μm Indentation speed: 200 nm / s Extraction speed: 200 nm / s Indenter used: Conical (spherical indenter: radius of curvature 10μm) Measurement method: Single indentation measurement Measurement temperature: 80℃

[0160] <Peel strength against acrylic sheet> The adhesive layer of the surface protection film (25mm wide x 140mm long), from which the release liner had been peeled off, was bonded to the surface of an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) using a 2kg hand roller in one pass-and-go motion, and left for 30 minutes at an ambient temperature of 23°C. The evaluation samples obtained as described above were measured using a tensile testing machine. The tensile testing machine used was the "Autograph AG-Xplus HS 6000mm / min high-speed model (AG-50NX plus)" manufactured by Shimadzu Corporation. The evaluation samples were set in the tensile testing machine and the tensile test was started. Specifically, the load when peeling the surface protective film from the acrylic plate was measured, and the average load at that time was defined as the peeling force of the surface protective film from the acrylic plate (peeling force against the acrylic plate). The conditions for the tensile test were: test environment temperature: 23℃, peeling angle: 180 degrees, peeling speed (tensile speed): 300mm / min.

[0161] <Adhesion strength to polyimide film> The adhesive layer of the surface protective film (25 mm wide x 140 mm long), from which the release liner had been peeled off, was bonded to the surface of the polyimide film (Yupi-Rex S, manufactured by Ube Industries, Ltd.) on a glass plate (soda-lime glass, manufactured by Matsunami Glass Industry Co., Ltd.) using a 2 kg hand roller in one back-and-forth motion, and left for 30 minutes at an ambient temperature of 23°C. The evaluation samples obtained as described above were measured using a tensile testing machine. The tensile testing machine used was the "Autograph AG-Xplus HS 6000mm / min high-speed model (AG-50NX plus)" manufactured by Shimadzu Corporation. The evaluation samples were set in the tensile testing machine and the tensile test was started. Specifically, the load when peeling the surface protective film from the glass plate with the polyimide film was measured, and the average load at that time was defined as the peeling force of the surface protective film from the polyimide film (adhesion force to the polyimide film). The conditions for the tensile test were: ambient temperature: 23°C, peeling angle: 180 degrees, peeling speed (tensile speed): 300 mm / min.

[0162] <Height of the raised edge at the laser-processed end> The laminates obtained in the examples and comparative examples were processed using a CO2 laser. The laser processing conditions are as follows. CO2 laser wavelength: 9.36 μm ·Processing speed: 500mm / sec • Frequency: 30Hz • Wattage: Adjusted according to the total thickness of the laminate so that the uncut portion of the processed product remained at 7 μm. Subsequently, the height of the raised edge at the laser-processed end was evaluated using a microscope (OLYMPUS BX51) according to the following procedure. The laser-processed end is the edge T of the base material portion of the reinforcing film at the laser-cut surface, as shown in Figure 3. (1) The laminate was cut to 10mm x 20mm so that the processed area was in the center, and the protective film portion on the surface of the cut laminate was peeled off. (2) After that, the laminate from which the surface protective film had been peeled off was placed vertically to the stage, the cross-section was observed, and the height of the raised edge at the laser-processed end was measured.

[0163] [Manufacturing Example 1] <Manufacturing of acrylic polymer A> In a four-necked flask equipped with a stirring blade, thermometer, nitrogen gas inlet tube, and condenser, 96 parts by weight of 2-ethylhexyl acrylate (2EHA), 4 parts by weight of 2-hydroxyethyl acrylate (HEA) as monomers, 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) as polymerization initiators, and 150 parts by weight of ethyl acetate were charged. Nitrogen gas was introduced while gently stirring, and the polymerization reaction was carried out for 6 hours while maintaining the liquid temperature in the flask at around 65°C to obtain a solution of acrylic polymer A with a weight-average molecular weight of 540,000.

[0164] [Manufacturing Example 2] <Manufacturing of acrylic polymer B> In a four-necked flask equipped with a stirring blade, thermometer, nitrogen gas inlet tube, and condenser, 95 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA) as monomers, and 0.2 parts by weight of 2,2'-azobisisobutyronitrile and 233 parts by weight of ethyl acetate as polymerization initiators were charged. Nitrogen gas was introduced while gently stirring, and the mixture was heated to 60°C. The polymerization reaction was carried out for 7 hours while maintaining the temperature of the liquid in the flask at around 60°C to obtain a solution of acrylic polymer B with a weight-average molecular weight of 600,000.

[0165] [Manufacturing Example 3] <Manufacturing of reinforcing films> 63 parts by weight of 2-ethylhexyl acrylate (2EHA), 15 parts by weight of N-vinyl-2-pyrrolidone (NVP), 9 parts by weight of methyl methacrylate (MMA), 13 parts by weight of 2-hydroxyethyl acrylate (HEA), 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 133 parts by weight of ethyl acetate as a polymerization solvent were placed in a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, the temperature was raised to 65°C and the reaction was allowed to proceed for 10 hours. Then, ethyl acetate was added to obtain an acrylic polymer solution with a solid content of 30% by weight. The weight-average molecular weight of the acrylic polymer in the obtained acrylic polymer solution was 800,000. Next, an isocyanate crosslinking agent (trade name "Takenate D110N", manufactured by Mitsui Chemicals, Inc.) was added to the above acrylic polymer solution in an amount equivalent to 1.1 parts by weight of solids per 100 parts by weight of acrylic polymer (solids), and a silane coupling agent (γ-glycidoxypropyltrimethoxysilane, trade name "KBM403", manufactured by Shin-Etsu Chemical Co., Ltd.) was added in an amount equivalent to 0.15 parts by weight of solids per 100 parts by weight of acrylic polymer (solids). An acrylic adhesive composition was then prepared by mixing these together. Next, the obtained acrylic adhesive composition was applied to one side of a PET (polyethylene terephthalate) substrate (75 μm thick) to form a coating layer on the PET substrate. Then, the PET substrate with the coating layer was placed in an oven and dried at 130°C for 3 minutes to create a 10 μm thick adhesive layer on one side of the PET substrate. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", 25 μm thick, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer to obtain a reinforcing film.

[0166] [Example 1] Acrylic polymer A: 100 parts by weight (solids), isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.): 5 parts by weight as a crosslinking agent, and Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.): 0.03 parts by weight as a catalyst were blended and diluted with ethyl acetate to obtain an acrylic adhesive composition with a total solids content of 20% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 50 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 10 μm, and cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer as a release liner to obtain a surface protective film (1). The obtained surface protection film (1) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (1), the adhesive layer of the surface protection film (1) was bonded to the substrate side of the reinforcing film manufactured in manufacturing example 3. After further peeling off the release liner of the reinforcing film, it was bonded to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (1). Laser processing was performed on the laminate (1), and the processed edges were evaluated. The results are shown in Table 1.

[0167] [Example 2] An acrylic adhesive composition was obtained by blending 100 parts by weight (solids) of acrylic polymer B and 6 parts by weight of a tetrafunctional epoxy compound (Tetrad C:T / C, manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent, and diluting with ethyl acetate to a total solids content of 15% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 5 μm. The film was cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer to obtain a surface protective film (2). The obtained surface protection film (2) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (2), the adhesive layer of the surface protection film (2) was laminated to the reinforcing film manufactured in manufacturing example 3. After peeling off the release liner of the reinforcing film, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (2). Laser processing was performed on the laminate (2), and the processed edges were evaluated. The results are shown in Table 1.

[0168] [Example 3] Acrylic polymer A: 100 parts by weight (solids), isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.): 5 parts by weight as a crosslinking agent, and Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.): 0.03 parts by weight as a catalyst were blended and diluted with ethyl acetate to obtain an acrylic adhesive composition with a total solids content of 20% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 10 μm. The film was cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer to obtain a surface protective film (3). The obtained surface protection film (3) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (3), the adhesive layer of the surface protection film (3) was laminated to the reinforcing film manufactured in manufacturing example 3. Furthermore, after peeling off the release liner of the reinforcing film, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (3). Laser processing was performed on the laminate (3), and the processed edges were evaluated. The results are shown in Table 1.

[0169] [Example 4] Acrylic polymer A: 100 parts by weight (solids), isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.): 4 parts by weight as a crosslinking agent, and Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.): 0.03 parts by weight as a catalyst were blended and diluted with ethyl acetate to obtain an acrylic adhesive composition with a total solids content of 20% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 20 μm. The film was cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer to obtain a surface protective film (4). The obtained surface protection film (4) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (4), the adhesive layer of the surface protection film (4) was laminated to the reinforcing film manufactured in manufacturing example 3. After peeling off the release liner of the reinforcing film, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (4). Laser processing was performed on the laminate (4), and the processed edges were evaluated. The results are shown in Table 1.

[0170] [Example 5] Acrylic polymer A: 100 parts by weight (solids), isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.): 4 parts by weight as a crosslinking agent, and Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.) 0.03 parts by weight as a catalyst were blended and diluted with ethyl acetate to obtain an acrylic adhesive composition with a total solids content of 20% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 21 μm. The film was cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer as a release liner to obtain a surface protective film (5). The obtained surface protection film (5) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (5), the adhesive layer of the surface protection film (5) was laminated to the reinforcing film manufactured in manufacturing example 3. After peeling off the release liner of the reinforcing film, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (5). Laser processing was performed on the laminate (5), and the processed edges were evaluated. The results are shown in Table 1.

[0171] [Example 6] Acrylic polymer A: 100 parts by weight (solids), isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.): 4 parts by weight as a crosslinking agent, and Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.): 0.03 parts by weight as a catalyst were blended and diluted with ethyl acetate to obtain an acrylic adhesive composition with a total solids content of 20% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 10 μm. The film was cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer to obtain a surface protective film (6). The obtained surface protection film (6) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (6), the adhesive layer of the surface protection film (6) was laminated to the reinforcing film manufactured in manufacturing example 3. After peeling off the release liner of the reinforcing film, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (6). Laser processing was performed on the laminate (6), and the processed edges were evaluated. The results are shown in Table 1.

[0172] [Comparative Example 1] After peeling off the release liner from the reinforcing film manufactured in manufacturing example 3, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (C1). Laser processing was performed on the laminate (C1), and the processed edges were evaluated. The results are shown in Table 1.

[0173] [Comparative Example 2] Acrylic polymer A: 100 parts by weight (solids), isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.): 5 parts by weight as a crosslinking agent, and Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.): 0.03 parts by weight as a catalyst were blended and diluted with ethyl acetate to obtain an acrylic adhesive composition with a total solids content of 20% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 100 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 10 μm. The film was cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a surface protective film (C2) was obtained by laminating the silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, to the surface of the obtained adhesive layer as a release liner. The obtained surface protection film (C2) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (C2), the adhesive layer of the surface protection film (C2) was laminated to the reinforcing film manufactured in manufacturing example 3. After peeling off the release liner of the reinforcing film, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (C2). Laser processing was performed on the laminate (C2), and the processed edges were evaluated. The results are shown in Table 1.

[0174] [Comparative Example 3] Acrylic polymer A: 100 parts by weight (solids), isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.): 5 parts by weight as a crosslinking agent, and Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.): 0.03 parts by weight as a catalyst were blended and diluted with ethyl acetate to obtain an acrylic adhesive composition with a total solids content of 20% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 10 μm. The film was cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer to obtain a surface protective film (C3). The obtained surface protection film (C3) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (C3), the adhesive layer of the surface protection film (C3) was laminated to the reinforcing film manufactured in manufacturing example 3. After peeling off the release liner of the reinforcing film, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (C3). Laser processing was performed on the laminate (C3), and the processed edges were evaluated. The results are shown in Table 1.

[0175] [Comparative Example 4] Acrylic polymer A: 100 parts by weight (solids), isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.): 4 parts by weight as a crosslinking agent, and Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.): 0.03 parts by weight as a catalyst were blended and diluted with ethyl acetate to obtain an acrylic adhesive composition with a total solids content of 20% by weight. The obtained acrylic adhesive composition was applied to a polyethylene terephthalate film (product name "T100", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 10 μm. The film was cured and dried at a drying temperature of 130°C for 30 seconds to produce an adhesive layer made of acrylic adhesive. Next, a silicone-treated side of a polyethylene terephthalate film (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation), which had one side treated with silicone, was laminated to the surface of the obtained adhesive layer to obtain a surface protective film (C4). The obtained surface protection film (C4) was aged at room temperature for 5 days. After peeling off the release liner of the surface protection film (C4), the adhesive layer of the surface protection film (C4) was laminated to the reinforcing film manufactured in manufacturing example 3. After peeling off the release liner of the reinforcing film, it was laminated to a 25 μm thick polyimide film (Ube Industries' "UPIREX S") to obtain a laminate (C4). Laser processing was performed on the laminate (C4), and the processed edges were evaluated. The results are shown in Table 1.

[0176] [Table 1] [Industrial applicability]

[0177] The optical component with a surface protective film of the present invention is suitably usable to impart rigidity and impact resistance to optical components included in optical devices where miniaturization is required. The optical laminate of the present invention is suitably usable in optical devices where miniaturization is required. The method for manufacturing the optical device of the present invention can be used as a method for manufacturing optical devices where miniaturization is required with high quality. [Explanation of symbols]

[0178] 1000 Optical components with surface protective film 2000 Other optical components 3000 optical laminate 100 Surface protective film (I) 200 Reinforcement film (II) 11 Base material (Ia) 12 Adhesive layer (Ib) 21 Base material (IIa) 22 Adhesive layer (IIb) T: Edge of the base material portion of the reinforcing film in the laser cross-section.

Claims

1. A method for manufacturing an optical device including an optical component, A process of bonding an optical component with a surface protective film to another optical component, A process of performing laser processing by irradiating the optical component with the surface protective film attached with a laser from the opposite side of the other optical component as viewed from the optical component, A step of re-peeling off the surface protective film after laser processing, Includes, The optical component with the surface protective film is An optical component with a surface protective film, comprising a surface protective film (I) and an optical component, The surface protective film (I) comprises a substrate (Ia) and an adhesive layer (Ib), The optical component is a reinforcing film (II), and the reinforcing film (II) comprises a substrate (IIa) and an adhesive layer (IIb). The adhesive layer (Ib) and the substrate (IIa) are directly laminated together. The thickness of the optical component is 400 μm or less. The thickness of the substrate (Ia) is 24 μm or more and less than 50 μm. The thickness of the adhesive layer (Ib) is 1 μm to 40 μm. The surface hardness of the adhesive layer (Ib) at 80°C is 0.05 MPa or more and 3.00 MPa or less. A method for manufacturing optical devices.

2. The method for manufacturing an optical device according to claim 1, wherein the adhesive layer (Ib) has a peel force against an acrylic plate of less than 0.25 N / 25 mm at a peel angle of 180° and a tensile speed of 300 mm / min in an environment of 23°C and 50% relative humidity.

3. The method for manufacturing an optical device according to claim 1, wherein the adhesive strength of the adhesive layer (IIb) to the polyimide film at a peel angle of 180° and a tensile speed of 300 mm / min in an environment of 23°C and 50% relative humidity is 3 N / 25 mm or more.

Citation Information

Patent Citations

  • JP1988066199A

  • Simple defroster

    JP1988075467A

  • Heat pump type air conditioner

    JP1989067551A

  • Lamination type polarizing plate and its manufacturing method

    JP2005189530A

  • Laminated polarizing plate and method of manufacturing the same

    JP2009086675A